Metodología para la estimación de kilómetros-vehículo recorrido kvr mediante ecuaciones lineales y sus aplicaciones en consumos energéticos de transporte (caso provincia de Loja). - Díaz Samaniego, Juan Pablo (2017)
This research aims to develop a novel methodology to estimate the indicator of KVT (kilometer vehicle traveled) useful for any ecuadorian region, the calculations were developed for the province of Loja in 2014; For which it was used the OLADE energy balance method joint to Hardy Cross hydraulic flow balance method. We assess and classified the indicators of automotive Loja fleet, antiquity, in addition were used indicators of fuel efficiency developed by INER as input to calculate KVT. During the development of this research we identified methodologies to calculate the KVT in some regions and the applicability to the ecuadorian case, we evaluated the information needed to create a model, we used the Hardy Cross iterative method to solve the incomplete equation system, it was needed the Excel Solver tool to generate the solution in a spreadsheet and plot results. This methodology was applied to the entire local province fleet and was validated with a sample of 40 taxis. These assesment allow to estimate the unjustified consumption in the complete energy system of transport through the application of the automotive use factor.